P605 Functional constipation in a tertiary hospital setting. (June 2019) - Milošić, Katarina; Aničić, Mirna Natalija; Omerza, Lana; Senečić-Čala, Irena; Vuković, Jurica; Tješić-Drinković, Duška
Abstract : Objectives: Functional constipation in children should be diagnosed in primary care, based on Rome criteria. Management in tertiary care is rarely needed. The aim of this study was to assess the frequency and structure of paediatric patients diagnosed with functional constipation in a tertiary hospital setting. Methods: This study enrolled children referred to the paediatric gastroenterologist (PG) at the UHC Zagreb from January 1st 2017 to December 31st 2017 (N=1729). Data on patients was extracted retrospectively from clinical records. The subjects were classified in three age groups: infants and toddlers (0–3 years), children (4–10 years) and adolescents (11–18 years). Descriptive statistics and chi-square test were used, statistical significance was determined as p<0.05 Results: After appropriate evaluation, about 8% of all outpatients seen by the PG at the UHC Zagreb during year 2017 had functional constipation with or without encopresis (7.63% or 132 patients, boys: 56, 1% vs girls: 43, 9%). Half of the patients were in the age group of 4 to 10 years (66/132 or 50%), about 1/3 was 0 to 3 years old (41/132), and about 1/5 were adolescents (25/132). It was the most common functional gastrointestinal disorder (FGID) (132/328 or 40.24%), both in girls and boys. Also, it was the leading FGID in the infant/toddler (41/57) and the children group (66/124). Retentive encopresis was present in about 1/5 of children (29/132 or 21.9%) Accompanied encopresis was mainly observed in the age group of 4–10 years (22/66 or 33.3%, χ²=9.9431, p<0.05). Also, encopresis tends to be more frequent among male patients with functional constipation (male, 27% vs female, 15.5%). In patients who visited PG for the first time, substantial discordance in the referral and the final diagnosis was observed. About 1/3 of patients with diagnosed constipation was referred with another diagnosis (29/92 or 31.5%). However, most of patients with constipation as referral diagnosis had the same disorder as final diagnosis (49/53 or 92.5%). Discussion: Frequency of functional constipation in paediatric patients in tertiary hospital setting, as well as sex and age distribution, is comparable to reported incidences in the population. The discordance of referral and final diagnosis shows that constipation is not adequately recognized in primary care, but when recognized, it is mostly diagnosed correctly. Conclusion: Functional constipation is not recognized enough in primary care and more efforts are needed to assure a positive diagnosis of this disorder prior to the referral to tertiary care.